2017
DOI: 10.1371/journal.pmed.1002356
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound non-invasive measurement of intracranial pressure in neurointensive care: A prospective observational study

Abstract: BackgroundThe invasive nature of the current methods for monitoring of intracranial pressure (ICP) has prevented their use in many clinical situations. Several attempts have been made to develop methods to monitor ICP non-invasively. The aim of this study is to assess the relationship between ultrasound-based non-invasive ICP (nICP) and invasive ICP measurement in neurocritical care patients.Methods and findingsThis was a prospective, single-cohort observational study of patients admitted to a tertiary neurocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
177
2
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(204 citation statements)
references
References 36 publications
(45 reference statements)
12
177
2
13
Order By: Relevance
“…The RF classifier can easily be extended to include categorical features, such as annotations about clinical interventions, the patient's medical history and lab results. Given modern multimodal brain monitoring systems, using additional measurements, such as the optic nerve sheath diameter [14], central venous pressure or near-infrared spectroscopy recordings, could uncover potential confounding factors and increase performance of the classifier further.…”
Section: Discussionmentioning
confidence: 99%
“…The RF classifier can easily be extended to include categorical features, such as annotations about clinical interventions, the patient's medical history and lab results. Given modern multimodal brain monitoring systems, using additional measurements, such as the optic nerve sheath diameter [14], central venous pressure or near-infrared spectroscopy recordings, could uncover potential confounding factors and increase performance of the classifier further.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the optic nerve sheath diameter (ONSD) by ultrasonography is a well-established surrogate marker for raised ICP in the clinical setting 12. Studies have shown that intracranial hypertension and elevated brain volume are associated with an increased ONSD, as the sheath surrounding the optic nerve presents a continuum to cerebral dura and subarachnoid mater 13.…”
Section: Introductionmentioning
confidence: 99%
“…Por muitos anos tentou-se avaliar a vasculatura cerebral com transdutores que emitem frequências de som de 4 MHz a 10 MHz, porém sem sucesso, pois a barreira óssea do crânio atenuava essas ondas. Em (Bellner et al, 2004;Cardim et al, 2017). Já outros trabalhos encontraram uma fraca correlação entre PIC e IP, concluindo ser este um método limitado para tal fim (Behrens et al, 2010;Cardim et al, 2016c;Morgalla e Magunia et al, 2016;Zweifel et al, 2012;).…”
Section: Avaliação Não Invasiva Da Pic: Doppler Transcranianounclassified
“…Por isso, nos últimos anos, há um grande número de estudos que visam a desenvolver diversas técnicas não invasivas para estimação da PIC (Bellner et al, 2004;Cardim et al, 2016c;Robba et al, 2017;Roh e Park 2016).…”
Section: Considerações Sobre As Correlações Da Pic Com Os Parâmetros unclassified
See 1 more Smart Citation